A review of the scientific contributions by Massimo Salvatores to nuclear reactor physics and engineering. (March 2021) - Palmiotti, Giuseppe; Ravetto, Piero
Abstract: Massimo Salvatores has been an eminent personality of the nuclear science community. He is universally recognized as one of the scientists who helped to maintain research excellence in the nuclear field throughout the past 50 years. His activity covers the theoretical aspects of nuclear reactor physics, the development of efficient computational methods and tools, and experimental analysis. This paper reviews the scientific production of Massimo Salvatores, highlighting what are believed to be his most relevant contributions to nuclear science and engineering.